Do Leadership and Motivation Impact Performance? Empirical Study at the Secretariat of the DPRD Residency of Surakarta City - Chandra Wardiyan; Purwanto; Yoppi Syahrial; Ariyani Wahyu Wijayanti (Universitas Muhammadiyah Palembang, 2025)
This study investigates the effect of leadership and motivation on employee performance at the Secretariat of the Regional People's Representative Council (DPRD) in the Surakarta Residency. A total of 105 respondents, including civil servants and contract employees, participated in the survey. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results of the hypothesis testing indicate that leadership has a significant and positive impact on employee performance. Similarly, motivation is also proven to have a significant positive effect on performance. These findings emphasize the strategic role of leadership in providing direction and empowerment, as well as the importance of motivation in encouraging responsibility and commitment. The tested model meets the criteria for validity, reliability, and overall model fit. The study supports the application of Goal Setting Theory and Maslow’s Hierarchy of Needs in enhancing public sector performance and recommends strengthening leadership capacity and motivation systems to improve organizational effectiveness.